Strategi Komunikasi Perempuan Hindu Dalam Pelestarian Budaya Tenun Cagcag Motif Gegambir Banjar Pesalakan Desa Pejeng Kangin, Gianyar - Kusuma Dewi, Made Ika; Pertu Agung, I Gusti Ngurah; Dharma Putra, Anggara Putu; Wahyu Arinatha, I Dewa Agung (Jayapangus Press, 2023)
The re-engagement of Hindu women in weaving Gegambir motif cagcag woven fabric is an important part of efforts to preserve the culture and tradition of weaving in Banjar Pesalakan, Pejeng Kangin Village. The Sari Bhakti Weaving Group is one of the few remaining Cagcag weavers in Pejeng Village Banjar Pesalakan after the Covid-19 pandemic. Socio-cultural changes as a result of tourism development make the scarcity of traditional weavers of Gegambir motif cagcag cloth This can threaten the sustainability of traditional economic activities. Therefore, it is necessary to protect and promote traditional weavers and local handicrafts so that they remain sustainable and become a sustainable tourist attraction. This phenomenon needs to be studied how Hindu women and weaving: communication strategies, especially the Sari Bhakti Weaving group in the preservation of the Cagcag motif Gegambir Weaving culture in Banjar Pesalakan. This study describes this research related to the role of Hindu women, especially the Sari Bhakti Weaving group towards the preservation of the Gegambir motif Cagcag Weaving, communication strategies in the preservation of the Gegambir motif Cagcag Weaving, and the impact of communication strategies in the preservation of the Gegambir motif Cagcag Weaving in Banjar Pesalakan, Pejeng Kangin Village. The use of communication strategies in the preservation of Tenun Cagcag motif Gegambir by the Sari Bhakti Weaving Group of Banjar Pesalakan has important implications and impacts to ensure the sustainability and appreciation of this cultural heritage. An effective communication strategy can help raise public awareness about the uniqueness and importance of the Cagcag motif Gegambir Weaving as part of the local cultural heritage. The information conveyed through this strategy can help the community understand the historical, aesthetic, and skill values embodied in the Gegambir motif Cagcag Weaving.